PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA MATA PELAJARAN MATEMATIKA - Kusnaeni; Paridjo; Munadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is often perceived as an abstract subject and disconnected from students' everyday lives. Through the Culturally Responsive Teaching (CRT) approach, it is expected that students will be able to understand mathematics, specifically the topic of data presentation in a way that relates to their daily experiences. Furthermore, Liveworksheets-based E-Worksheets (E-LKPD) are needed to support 21st-century mathematics learning. The purpose of this article is to develop Liveworksheets-based E-Worksheets using a Culturally Responsive Teaching approach in mathematics instruction. The method used is Research and Development (R&D). The results of this development show that: (1) the validity of the Liveworksheets-based E-Worksheets using the CRT approach reached a validity percentage of 90.87%, which falls into the "very valid" category, and (2) the practicality of the product reached a practicality percentage of 95%, categorized as "very practical." Therefore, the developed Liveworksheets-based E-Worksheets using the Culturally Responsive Teaching approach are valid and practical for use in teaching the topic of data presentation in Phase D mathematics at SMP Negeri 6 Tegal.